THE BUSINESS STRATEGIC PLAN FOR RSD KOLONEL ABUNDJANI BANGKO YEAR 2019 – 2023 - Arismen Arismen; Amal Chalik Sjaaf (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The progress of the hospital industry now requires effective management to improve the quality and quality of service appropriate to the standard goals. Preparation of this business strategic plan should involve decision-maker in hospitals and existing organizational resources efficiently and effectively by taking into account current conditions. This study aims to provide a comprehensive review of the process of preparing a hospital business strategic plan so that an alternative strategy can be obtained for the next 5 years. Methods: This study was used operational research, qualitative method with in-depth interviews and hospital performance reports analysis. External and internal environment factors included finance, customer, demographics, geography, policy, marketing, information system, human resources, physical facility and organization were used as evaluated variables. SWOT analysis and Balanced Scorecard framework were used to identify critical success management factors. The Consensus Decision Making Group (CDMG) matrix were used to determined factor evaluation matrix as a final score. Results: Based on an analysis of external and internal environmental factors, alternative strategies that are suitable for current hospital conditions are market penetration and service product development. In order to realize this strategy there are several things that must be of particular concern, namely the limited resources that are available which include the availability of human resources and financial support and there is no available integrated hospital information system. Conclusion: The business strategy plan recommended for developing RSD Kolonel Abundjani Bangko’s services for the next 5 years is market penetration and service product development. In order to realize this strategic plan requires a strong commitment from all human resources in the hospital and related stakeholders.